Bybelvertalers en Bybelvertalings die afgelope honderd jaar, in besonder vanuit die Fakulteit Teologie van die Universiteit van Pretoria - Geyser-Fouché, Ananda (HTS teologiese studies, 2017)
With the 500 year celebration of the Reformation, it is necessary that Bible translation be reviewed again. The year 2017 is not only the year of Reformation celebration, but also the year of centenary celebration of the Faculty of Theology at the University of Pretoria (UP). The article attempts to briefly refer to the roots of Bible translation, which is anchored in the Reformation; but also to look at Bible translation in South Africa over the last hundred years, as well as the contribution made especially by the Faculty of Theology at the University of Pretoria (UP) in this regard.